2020
DOI: 10.3389/fpls.2020.569687
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Root Growth Under Combined Arsenic and Hypoxia Stress Is Linked to Nutrient Deprivation

Abstract: Root architecture responds to environmental stress. Stress-induced metabolic and nutritional changes affect the endogenous root development program. Transcriptional and translational changes realize the switch between stem cell proliferation and cell differentiation, lateral root or root hair formation and root functionality for stress acclimation. The current work explores the effects of stress combination of arsenic toxicity (As) and hypoxia (Hpx) on root development in Arabidopsis thaliana. As revealed prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 137 publications
0
12
1
Order By: Relevance
“…Indeed, root apical meristem is the major absorption area involved in As(III) uptake (Ashraf et al, 2019). It is somehow surprising that, in contrast to our results (Catarecha et al, 2007), in two independent studies, it was found that arsenic induces root hair elongation (Bahmani et al, 2016;Kumar et al, 2020).…”
Section: Hormones Root Architecture and Arsenic Responsecontrasting
confidence: 83%
See 1 more Smart Citation
“…Indeed, root apical meristem is the major absorption area involved in As(III) uptake (Ashraf et al, 2019). It is somehow surprising that, in contrast to our results (Catarecha et al, 2007), in two independent studies, it was found that arsenic induces root hair elongation (Bahmani et al, 2016;Kumar et al, 2020).…”
Section: Hormones Root Architecture and Arsenic Responsecontrasting
confidence: 83%
“…Root architecture is an essential element in soil resource acquisition and, therefore, it is a primary determinant to prevent arsenic uptake. Arsenic exposure triggers specific developmental responses, being a major factor for plant survival to arsenic (Bahmani et al, 2016;Kumar et al, 2020;Yadav et al, 2021). Toward this, it is essential for plants to exhibit finely tuned regulatory circuits that integrate arsenic uptake, extrusion or sequestering with plant growth developmental programs, particularly in roots.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in a recent study on the combination of high light and heat stress it was found that heat stress-driven regulation of stomata (stomata opening) overcomes high light-driven stomata regulation (stomata closure) to result in stomata opening during the stress combination [47]. In addition to stomatal responses, root architecture is also altered during a stress combination [58,59], and nutrient availability plays a key role in this response [58,60,61]. In addition to studies examining the simultaneous exposure of plants to two or more stresses (described in the preceding text), studies of sequential exposure of plants to different stresses, or their combination, revealed a similar complexity in plant responses to a stress combination [61][62][63].…”
Section: The Impact Of Multifactorial Stress Combinations On Plant Mementioning
confidence: 99%
“…A suitable example is the control of root architecture for optimized nutrient foraging under the impact of single or combinatorial stresses (Li 2021, Kumar et al 2020. The effect of hormones on root patterning differs among species and genotypes (Ristova et al 2018).…”
Section: Small Molecules Are Central To the Control Of Acclimationmentioning
confidence: 99%
“…Exogenous addition of H2O2 stimulates lateral root formation (Su et al 2016). Changes in glutathione redox potential occur within minutes after transfer of Arabidopsis thaliana to hypoxic conditions and together with ROS appear to shape the root system especially if combined with arsenic stress (Kumar et al 2019(Kumar et al , 2020. These examples prove the existence of an elaborate network of interacting signalling molecules.…”
Section: Small Molecules Are Central To the Control Of Acclimationmentioning
confidence: 99%